(untitled) (Research, Society and Development, 2022)
Objective: Identifying care provided to newborns in the first hour of life in two public maternity hospitals. Methodology: A quantitative, cross-sectional, descriptive study, aligned with a cohort, with 299 women attended in two public maternity hospitals in a municipality in the North of the State of Paraná, conducted from August to December 2017. Results: In the first hour of life, 70% of the babies were placed in skin-to-skin contact, among the reasons for not performing cesarean section with 54.4%. At birth 79.3% of the newborns were placed to suck in the mother’s breast. 86.3% newborns were submitted to interventions, 94.2% of which underwent nasopharynx and oropharynx aspiration. Conclusion: Care for the newborn has been occurring, requiring some improvement. Skin-to-skin contact and placement of the baby to suck the mother’s breast had expressive indexes but did not reach its entirety. The cesarean route and the high number of interventions were a hindrance to some care.